الفعالية المضادة للأحياء المجهرية لأغشية معزول بروتين الشرش المدعمة بمستخلص الشاي الأخضر واستخدامها في حفظ الجبن الطري - جلوب، كرم خالد; عبدالرحمن، سوسن مصطفى (جامعة بغداد - مركز بحوث السوق وحماية المستهلك, 2018)
هدف البحث الحالي إلى دراسة تأثير إضافة مستخلص الشاي الأخضر إلى الأغشية المحضرة من معزول بروتين الشرش على الفعالية المضادة للأحياء المجهرية وتقييم فعالية هذه الأغشية على الجبن الطري العراقي المغطى بها خلال تسعة أيام من الخزن كبديل عن الأغلفة التجارية. في بداية الدراسة تم قياس تركيز الحد الأدنى للتثبيط عن طريق قياس قطر الهالة المتكونة نتيجة الثبيط لنمو البكتريا وشملت مجموعة البكتريا السالبة لصبغة غرام (Salamonella spp, Pseudomnas Aeuroginasa, Escherichia Coli) ومجموعة البكتريا الموجبة لصبغة كرام (Bacillus spp, Staphylococcus. Aureus) بالإضافة إلى خميرة (Candida. Albican) حيث بلغت أقطار الهالات المتكونة (16 , 14 , 7 , 10 , 20 , 11) على التوالي. وتمت ملاحظة التغيرات في الأعداد الميكروبية خلال مدة الخزن حيث استعمل في هذه الدراسة معاملتين من الجبن الطري العراقي، كانت المعاملة الأولى للجبن الغير مغلف وهي معاملة السيطرة (معاملة T1) أما المعاملة الثانية من الجبن (معاملة T2) فكانت مغلفة بأغشية بروتينات الشرش المدعمة بمستخلص الشاي الأخضر، وكانت نتائج التجارب التي أجريت لتقدير أعداد الأحياء المجهرية تشير إلى أن هناك فروق معنوية في الأيام الأخيرة من الخزن بين المعاملتين وعلى مستوى معنوي 0.05 في كلا من العدد الكلي للبكتريا وبكتريا القولون والعنقوديات الذهبية فقد انخفضت الأعداد إلى ما يقارب 1-2 لوغارتم وحدة تكوين مستعمرة/ غم وما يقارب 2-3 لوغارتم وحدة تكوين مستعمرة/ غم بالنسبة إلى البكتريا العنقوديات الذهبية وتبين أن هناك أيضا فروق معنوية وعلى مستوى معنوي 0.05 بين المعاملة T2 لنماذج الجبن الطري العراقي مقارنة مع المعاملة T2 لأعداد البكتريا المحبة للبرودة وكان الانخفاض في الأعداد يقارب 2-3 لوغارتم وحدة تكوين مستعمر/ غم وأعداد الأعفان والخمائر انخفضت بمقدار 0.5 – 1.5 لوغارتم وحدة تكوين مستعمرة/ غم الطري. قد أدت معاملة تغليف الجبن إلى زيادة العمر الخزني للجبن وعكست نتائج التقويم الحسي للمعاملتين T1 (الجبن غير المغلف) و T2 تفوق الجبن المغلف بحصوله على درجات أعلى خلال فترة الخزن.
The aim of the current research is to study the effect of adding green tea to the edible film prepared from the whey protein isolate on the effectiveness of microorganisms and evaluating the of antimicrobial effectiveness of these films on Iraqi soft cheese packaging during the nine days of storage as an alternative to commercial packaging. At the beginning of the study, the minimum inhibitory concentration was measured by calculate the diameter of the zone of inhibition on growth of the bacteria and it's included the group of Gram negative bacteria (Escherichia coli, Salmonella spp, Pseudomonas Aeruginosa) and the group of Gram positive bacteria (Staphylococcus Aureus, Bacillus spp) and a yeast (Candida Albican). Where the diameter of the halos formed (11, 20, 10, 7, 14, 16) respectively. The changes in the microbial numbers were also observed during the storage period. In this study, two treatments of Iraqi soft cheese were used. The first treatment of the cheese was uncoated as a control treatment (T1 treatment) & the second treatment of the cheese (T2 treatment) was coated with the film of the whey protein supported by the green tea extract. The results of the experiments were conducted to estimate the numbers of microorganisms indicate that there are significant differences in the last days of storage Between the two treatments and at a significant level of 0.05 in both the total count bacteria and total coliform bacteria and staphylococcus number, The numbers of bacteria have decreased about 1-2 Logarithmic CFU/gm, and approximately 2-3 Logarithmic CFU/gm in relation to the number of staphylococcus aureus. It was also found that there were significant differences at a significant level of 0.05 Between the T2 treatment of Iraqi soft cheese models compared to the T2 treatment for the number of sychrotrophic bacteria and the reduction in numbers was approximately 2-3 Logarithmic CFU/gm, and the number of molds and yeast decreased by 0.5-1.5 Logarithmic CFU/gm, The treatment of cheese packaging has increased the age of cheese the results of the sensory evaluation of T1 (non-coated cheese) and T2 were improved that the coated cheese was obtained a higher grades during the storage period.
Keywords: الشاي الاخضر -- اغلفة قابلة للاكل -- بروتین الشرش -- الجبن الطري العراقي